Aprendizagem em ambientes multitarefas. Uma realidade na Cultura Maker - Rodrigues do Nascimento, Ernandes; Lima de Brito , Isabel Pauline; Pereira da Silva , Arlaine Gabriela (Journal of Learning Styles, 2020)
Learning scenarios need to be part of the process of providing students with environments that can favor their creativity, performance and attention, always respecting the learning styles they have. So, how do students feel when they live the experience of learning in a multitasking environment, common in places designed to provide a maker education? The general objective of examining the experience of graduate students when participating in the discipline Active and Innovative Methodologies in a FabLab, a multitasking and disruptive environment, belonging to the context of the maker culture, its relationship with their learning styles and the level of engagement during classes. In addition, the research had as specific objectives: to know the learning styles and the levels of engagement of the students; describe the experience of studying in multitasking environments, following a learning proposal through enchantment. The results showed that the predominant learning style of the respondents was divergent, with those who lost the most focus during classes being divergent, but the vast majority of students said they did not find it confusing to study in a disruptive environment. Practically all participants were engaged in the behavioral dimension and the agency dimension had the lowest level of engagement.
Keywords: Multitasking environment; Cultura Maker; Learning Styles; Entrepreneurship; Learning through Entrepreneurship